Inovasi Pembelajaran PAI Melalui Metode Problem Based Learning untuk Menstimulasi Kemampuan Berpikir Kritis Siswa di SMA Darut Taqwa - Hisbadiana Maulidia; Muhammad Nur Hadi; Anang Sholikhudin; Achmad Yusuf (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Learning Islamic Religious Education (PAI) is an integral part of the educational curriculum which aims to shape students' morals, morals and spirituality. However, the challenge in learning PAI is how to develop students' critical thinking abilities, which are important skills in dealing with various life problems. The Problem Based Learning (PBL) method has been known to be effective in stimulating students' critical thinking abilities by presenting real problems that require solutions through processes of analysis, synthesis and evaluation. Innovations in PAI learning through PBL emphasize giving students a more active role in exploring and understanding the context of the Islamic religion through challenges and problems that are relevant to everyday life.This research aims to explore and implement the PBL method in PAI learning with a focus on stimulating students' critical thinking abilities. Through this approach, students are directed to identify, analyze, and solve problems related to Islamic religious principles, as well as consider the ethical and moral implications of the solutions they propose. The methods used in this research include observation, interviews, and content analysis to evaluate the effectiveness of PAI learning innovations through PBL. The research results show that this method can improve students' critical thinking skills, increase their understanding of the principles of the Islamic religion, and facilitate the development of critical attitudes towards religious and moral issues. In conclusion, PAI learning innovation through PBL is an approach that has the potential to stimulate students' critical thinking abilities, deepen their understanding of Islamic religious values, and prepare them to face moral and spiritual challenges in their lives.